The role of change management in improving policy effectiveness in the SANDF - Pietersen, Jaco; Steyn, Pieter G; Meyer, Jan Abraham (Scientia Militaria - South African Journal of Military Studies, 2020)
Armed forces the world over have three primary functions – force development, force deployment and force employment. Defence policy plays a guiding role in all of these, but it is especially important in establishing the rationale for the creation of credible military deterrence. Usually, a defence policy presupposes the development of armed forces that are effective at executing their mandate, a condition that is measurable in terms of the discipline, skill and quality of the organisation. The study on which this article reports, used this concept to describe how change management – especially by focusing on incorporating effective prioritisation – could enhance the current defence policy. A general analysis of South African defence policy publications indicates that, indeed, the policymakers had thoroughly considered the effectiveness of the armed forces when they wrote the White Paper on Defence of 1996 and the Defence Review of 1998. By 2006, the South African Army had interpreted national defence policy and formulated a future strategy of its own very much in alignment with the ‘modern system’ approach of the original policy publications. The present study suggests that the principal reason for the large variance between defence policy, military capabilities, and real operational demands stems from the lack of effective prioritisation of defence. This article, therefore, concludes that the South African National Defence Force (SANDF) has been largely unsuccessful in complying with the demands of defence policy, irrespective of the fact that the policy by itself may be obsolete and/or inappropriate for the South African context. Furthermore, it is concluded that military effectiveness in meeting current operational demands is also doubtful. Finally, the schizophrenic organisational culture of the defence force may be the primary cause of its moving ever closer to reneging on its constitutional mandate.